2011
DOI: 10.1111/j.1399-0004.2011.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

FOXG1 mutations in Japanese patients with the congenital variant of Rett syndrome

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder characterized by microcephaly, psychomotor regression, seizures and stereotypical hand movements. Recently, deletions and inactivating mutations in FOXG1, encoding a brain-specific transcription factor that is critical for forebrain development, have been found to be associated with the congenital variant of RTT. Here we report the clinical features and molecular characteristics of two cases of the congenital variant of RTT. We conducted mutation scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…Including this study, 26 point mutations, 25 CNVs, and 2 t(2;14) balanced translocations have been reported in patients with a FOXG1-related phenotype. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22] The male-to-female ratios is 7/26 (27%) for point mutations and 13/25 (52%) for CNVs. The preponderance of females in patients positive for a FOXG1 point mutation is most probably due to the initial description of FOXG1 deleterious alleles in females with congenital RTTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including this study, 26 point mutations, 25 CNVs, and 2 t(2;14) balanced translocations have been reported in patients with a FOXG1-related phenotype. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22] The male-to-female ratios is 7/26 (27%) for point mutations and 13/25 (52%) for CNVs. The preponderance of females in patients positive for a FOXG1 point mutation is most probably due to the initial description of FOXG1 deleterious alleles in females with congenital RTTs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6]17 The same c.256dupC frameshift has already been reported twice in patients with congenital RTT. 7,18 The c.256del/dup is the second mutational hot spot affecting a mononucleotide repeat in FOXG1. We also describe five new CNVs in 14q12 in two males and three females.…”
Section: Discussionmentioning
confidence: 99%
“…17 Philippe et al, 25 Le Guen et al, 24,35 Mencarelli et al, 15 Bahi-Buisson et al, 16 Takahashi et al 26 …”
Section: Chromosomal Microarray Analysis Methodsunclassified
“…The mutation has been previously identified in both a female and a male with congenital variant of Rett syndrome. 24,26 Screening of the same 32 patients did not reveal any pathogenic mutations in PRKD1, a protein kinase involved in extracellular receptor-mediated signal transduction pathways. A number of known nonpathogenic polymorphisms were identified and shown in Table 2.…”
Section: Chromosomal Microarray Analysismentioning
confidence: 96%
“…NF-L is a neuron-specific cytoskeletal gene, 30 and Foxg1 is a gene that encodes for a transcription factor that is important for brain development and has been recently identified to be deleted or inactivated in Rett syndrome. 31,32 MeCP2 mRNA was also assessed in order to ensure that expression levels returned to normal two weeks following the infusions on PN0-2, as previously shown in reference 14. There was no effect of neonatal MeCP2 siRNA on the expression of any of these genes.…”
Section: Experiments 1: a Transient Reduction Inmentioning
confidence: 99%